Tourism, Personality, and Risky Behaviors Among Ukrainian Adolescents - Hryhorczuk, Nicholas; Zvinchuk, Alexander; Shkiriak-Nyzhnyk, Zoreslava; Slobodchenko, Liudmyla; Matsola, Alla; Hryhorczuk, Daniel (Turizam, 2019)
The aim of this paper was to determine whether engagement in tourism is associated with risky behaviors among Ukrainian adolescents. The study population consisted of 1075 adolescents who were enrolled in the Family and Children of Ukraine birth cohort study. They self reported how they prefer to spend their leisure time as well as their smoking, drinking, and sexual behaviors. The adolescents also completed the revised Eysenck Personality Inventory (EPI). Engagement in tourism was not associated with smoking or alcohol use. It was associated with ever had sex (OR=1.63; p=0.022) and had sex within the past 30 days (OR=1.67; p=0.037). These associations were stronger for males than females. Adolescents who had ever had sex and those who had sex within the past 30 days had significantly higher extraversion scores on the EPI than adolescents who had not (18.16 vs 16.65; p=0.002 and 18.45 vs 16.72; p = 0.002, respectively). In multivariable analyses, ever having sex and having sex within the past 30 days were significantly associated with male gender, age, and extraversion but not with tourism. We conclude that among Ukrainian adolescents, the association between engagement in tourism and sexual behavior is driven by personality, specifically higher extraversion.